Penafsiran Ayat-Ayat tentang Birrul Walidain - Aulia Khairunnisa Siregar; Siti Nur Aisyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Birrul Walidain is a concept in Islam that emphasizes the importance of filial piety and treating parents well. This term comes from the words